Political and economic ideas of Karl Marx in the contemporary context - Rocha Valencia, Alberto (2024)
Marx, in works such as "The 18th Brumaire of Louis Bonaparte", "The Class Struggle in France" and "The German Ideology", exposes his vision of the State as a bureaucratic-military, centralized and coercive machine. He identifies the State as an instrument of class domination, structurally related to capital. Distinguishes between political regimes, highlighting the bourgeois Monarchy and the Republic as forms of bourgeois domination. Analyzes the Paris Commune as an example of workers' self-government and absorption of the State. He considers civil society as the engine of history and advocates workers' self-organization as the basis for transforming it and extinguishing the State. Marx focuses his thinking on "Capital", his magnum opus on the analysis of capitalism. Book I, published, deals with capitalist production and surplus value, while volumes II and III were completed by Engels. In II, he analyzes the circulation of capital and simple and extended reproduction. In III, he studies capitalist production and the organic composition of capital, substantiating the Law of the Decreasing Tendency of the rate of profit. Marx links the cyclical crises of capitalism with the capital/labor contradiction, anticipating a possible socialist revolution led by the proletariat.